Application of Treated Palm Oil Fuel Ash (POFA) in Paint Production - bin Hazlan, Muhammad Aizad Husni; Mohd Zaky Noh; Rahimi L. Muhamud (Enhanced Knowledge in Sciences and Technology, 2024)
Paint manufacturing is a big industry that is important in several industries, including building, automotive, and home decoration. This project is about to improve the problem occur in paint production by producing an optimum thermal insulation paint using Palm Oil Fuel Ash (POFA) powder. POFA powder initially grind for three days to obtain the finer powder particle before being sieve using a 50 micrometer sieve shaker. The POFA powder undergoes two types of treatment which are heat and acid treatment to improve the pozzolan characteristic of POFA by eliminating carbon content, thus increase thermal insulation characteristics. The powder then will be mixed with other chemicals using Kakuhunter mixer for 1 minute. The paint mixture is include POFA, Calcium Carbonate (CaCO3) and other chemicals. The main finding for this project is to examine the final temperature between the paint mixture that had been filled with POFA, besides analyzing the heat capacity of the paint mixture using different composition of POFA powder, 25%, 50%, 75% and 100%. The results gives the differences of final temperature between each paint mixture after exposed to heat for 15 minutes.